When NIPT meets WES, prenatal diagnosticians face the dilemma: genetic etiological analysis of 2,328 cases of NT thickening and follow-up of pregnancy outcomes - Ji, Xueqi; Li, Qiongmei; Qi, Yiming; Wang, Xingwang; Ding, Hongke; Lu, Jian; Zhang, Yan; Yin, Aihua (Frontiers in Genetics, 2023)
Objective: To assess the performance of diverse prenatal diagnostic approaches for nuchal translucency (NT) thickening and to investigate the optimal prenatal screening or diagnostic action with a NT thickening of 95th percentile-3.50 mm. Methods: A retrospective analysis of 2,328 pregnancies with NT ≥ 95th percentile through ultrasound-guided transabdominal chorionic villus sampling (CVS), amniocentesis, or cordocentesis obtained clinical samples (chorionic villi, amniotic fluid, and cord blood), and real-time quantitative fluorescent PCR (QF-PCR), chromosome karyotyping (CS), chromosome microarray analysis (CMA), or whole exome sequencing (WES) were provided to identify genetic etiologies. Results: In this study, the incidence of chromosomal defects increased with NT thickness. When NT ≥ 6.5 mm, 71.43% were attributed to genetic abnormalities. The 994 gravidas with fetal NT thickening underwent short tandem repeat (STR), CS, and CMA. In 804 fetuses with normal karyotypes, CMA detected 16 (1.99%) extra pathogenic or likely pathogenic copy number variations (CNVs). The incremental yield of CMA was only 1.16% (3/229) and 3.37% (10/297) in the group with NT 95th percentile-2.99 mm and NT 3.0–3.49 mm, separately. Among the 525 gravidas with fetal NT thickening who underwent STR, CMA, and WES, the incremental yield of WES was 4.09% (21/513). In the group of NT 95th percentile-2.99 mm, there were no additional single-nucleotide variations (SNVs) detected in WES, while in 143 cases with NT of 3.0–3.49 mm, the incremental yield of WES was 5.59% (8/143). Conclusion: In the group of NT 95th percentile-3.0 mm, since chromosomal aneuploidy and chromosomal copy number variation were the primary causes and the additional contribution of CMA and WES was not significant, we recommend NIPT-Plus for pregnant women with a NT thickening of 95th percentile-3.0 mm first. In addition, comprehensive prenatal genetic testing involving CMA and WES can benefit pregnancies with NT thickening of 3.0–3.49 mm.